2017
DOI: 10.3389/fnana.2017.00004
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic and Postnatal Expression of Aryl Hydrocarbon Receptor mRNA in Mouse Brain

Abstract: Aryl hydrocarbon receptor (AhR), a member of the basic helix-loop-helix-Per-Arnt-Sim transcription factor family, plays a critical role in the developing nervous system of invertebrates and vertebrates. Dioxin, a ubiquitous environmental pollutant, avidly binds to this receptor, and maternal exposure to dioxin has been shown to impair higher brain functions and dendritic morphogenesis, possibly via an AhR-dependent mechanism. However, there is little information on AhR expression in the developing mammalian br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…In invertebrates, AhR homologs are implicated in dendrite branching in neurons: in Drosophila , the loss of function of the AhR homolog ( spineless ) promotes more complex dendritic arborization in sensory neurons ( Crews and Brenman, 2006 ; Kim et al, 2006 ); in C. elegans , ahr-1 mutant (AhR homolog) neurons also turn into a highly branched architecture ( Smith et al, 2013 ). In mammals, AhR is expressed in the adult brain ( Kimura and Tohyama, 2017 ), and its constitutive activation drastically reduces dendritic arborization and aberrant neuronal positioning in cortical pyramidal neurons and olfactory bulb interneurons ( Kimura et al, 2016, 2017 ; Kimura and Tohyama, 2017 ). AhR mRNA is also expressed in the dentate gyrus (DG) granule cells of the adult hippocampus ( Kimura and Tohyama, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In invertebrates, AhR homologs are implicated in dendrite branching in neurons: in Drosophila , the loss of function of the AhR homolog ( spineless ) promotes more complex dendritic arborization in sensory neurons ( Crews and Brenman, 2006 ; Kim et al, 2006 ); in C. elegans , ahr-1 mutant (AhR homolog) neurons also turn into a highly branched architecture ( Smith et al, 2013 ). In mammals, AhR is expressed in the adult brain ( Kimura and Tohyama, 2017 ), and its constitutive activation drastically reduces dendritic arborization and aberrant neuronal positioning in cortical pyramidal neurons and olfactory bulb interneurons ( Kimura et al, 2016, 2017 ; Kimura and Tohyama, 2017 ). AhR mRNA is also expressed in the dentate gyrus (DG) granule cells of the adult hippocampus ( Kimura and Tohyama, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, AhR is expressed in the adult brain ( Kimura and Tohyama, 2017 ), and its constitutive activation drastically reduces dendritic arborization and aberrant neuronal positioning in cortical pyramidal neurons and olfactory bulb interneurons ( Kimura et al, 2016, 2017 ; Kimura and Tohyama, 2017 ). AhR mRNA is also expressed in the dentate gyrus (DG) granule cells of the adult hippocampus ( Kimura and Tohyama, 2017 ). In this area, although it has been reported that AhR might modulate hippocampal neurogenesis ( Latchney et al, 2013 ), its role in the modulation of dendrite branching and plasticity in adult hippocampal newborn granule neurons remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…elegans and Drosophila [ 21 – 23 ] as well as to the regulation of dendritic morphology in subneocortical hippocampal pyramidal and olfactory granule neurons [ 37 , 48 ] and to cerebellar neurogenesis [ 24 ]. Expression of AhR transcripts has been reported in rodent brain regions, including the cerebral cortex and hippocampus [ 16 , 17 ]. Abnormal dendritic morphology of hippocampal CA1 neurons was shown in both TCDD-exposed and CA-AhR-transfected mice [ 37 ], suggesting that AhR is expressed in hippocampal pyramidal neurons and that its signaling is associated with dendritic growth.…”
Section: Discussionmentioning
confidence: 99%
“…The aryl hydrocarbon receptor (AhR), which belongs to the bHLH-PAS subfamily, is expressed in the mammalian brain, including the cerebral cortex in the developing and adult stages [ 16 – 18 ], and acts as a receptor for ligands to induce downstream signaling. The liganded AhR is activated by cofactors and translocated from the cytoplasm to the nucleus, where it enhances the transcription of target genes such as Cyp1a1 , Cyp1b1 , and Ahr repressor ( Ahrr ) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…AhR activation, which is the canonical mode of action for TCDD, is the distinguishing feature of DL PCBs. AhR-dependent signaling is implicated in the regulation of neurodevelopment in rodent models [166,167]. Altered patterns of neuronal cell proliferation, migration, and maturation have been observed in Ahr -/mice [168,169] and in mice genetically engineered to express constitutively active AhR [170].…”
Section: Arylhydrocarbon Receptor (Ahr) As a Molecular Target In Pcb mentioning
confidence: 99%